The stranger from the sea : a novel of Cornwall 1810-1811 - Graham, Winston (Pan Books, 2008)
The Poldark family awaits the return of Ross from his mission to Wellington's army in Portugal. But their ordered existence ends with Jeremy Poldark's dramatic rescue of a stranger from the sea. Stephen Carrington's arrival in the Poldark household changes all their lives. For Clowance and Jeremy in particular, the children of Ross and Demelza, Stephen's advent is the key to a new world-- one of both love and danger.